Salt Restriction Leads to Activation of Adult Renal Mesenchymal Stromal Cell–Like Cells via Prostaglandin E2 and E-Prostanoid Receptor 4. Issue 5 (May 2015) - Yang, Yanqiang; Gomez, Jose A.; Herrera, Marcela; Perez-Marco, Romelia; Repenning, Peter; Zhang, Zhiping; Payne, Alan; Pratt, Richard E.; Koller, Beverly; Beierwaltes, William H.; Coffman, Thomas; Mirotsou, Maria; et al.
<x xml:space="preserve">Abstract</x> Despite the importance of juxtaglomerular cell recruitment in the pathophysiology of cardiovascular diseases, the mechanisms that underlie renin production under conditions of chronic stimulation remain elusive. We have previously shown that CD44+ mesenchymal-like cells (CD44+ cells) exist in the adult kidney. Under chronic sodium deprivation, these cells are recruited to the juxtaglomerular area and differentiate to new renin-expressing cells. Given the proximity of macula densa to the juxtaglomerular area and the importance of macula densa released prostanoids in renin synthesis and release, we hypothesized that chronic sodium deprivation induces macula densa release of prostanoids, stimulating renal CD44+ cell activation and differentiation. CD44+ cells were isolated from adult kidneys and cocultured with the macula densa cell line, MMDD1, in normal or low-sodium medium. Low sodium stimulated prostaglandin E2 production by MMDD1 and induced migration of CD44+ cells. These effects were inhibited by addition of a cyclooxygenase 2 inhibitor (NS398) or an E-prostanoid receptor 4 antagonist (AH23848) to MMDD1 or CD44+ cells, respectively. Addition of prostaglandin E2 to CD44+ cells increased cell migration and induced renin expression. In vivo activation of renal CD44+ cells during juxtaglomerular recruitment was attenuated in wild-type mice subjected to salt restriction in the presence of cyclooxygenase 2 inhibitor rofecoxib. Similar results were observed in E-prostanoid receptor 4 knockout mice subjected to salt restriction. These results show that the prostaglandin E2/E-prostanoid receptor 4 pathway plays a key role in the activation of renal CD44+ mesenchymal stromal cell–like cells during conditions of juxtaglomerular recruitment; highlighting the importance of this pathway as a key regulatory mechanism of juxtaglomerular recruitment.